Prevention and Surgical Management of Postburn Contractures of the Hand - Fufa, Duretti T. (Springer US, 2013)
In addition to burn surgeons, skilled nurses, and therapists, hand surgeons are a key part of the multidisciplinary team caring for patients following thermal injury to the hand. Despite appropriate initial treatment and compressive therapy, contractures are common after deep burn. The most common and functionally limiting are web space and hand contractures. Web space contractures can be managed with excision followed by local soft tissue rearrangement or skin grafting. The classic burn claw hand deformity includes extension contracture of the metacarpophalangeal joints and flexion contractures of the proximal interphalangeal joints. The mainstay of management of these postburn contractures includes complete surgical release of scar tissue and replacement by full-thickness skin graft. In cases in which scar contracture release results in major exposure of the tendons or joints, distant tissue transfer is required. This review focuses on prevention and management of late sequelae of thermal injury to the hand focusing on contractures of the webspaces and hand.